Detention of doom / 3. - Fridolfs, Derek (DC Comics Secret Hero Society, 2018)
"When Lex Luthor's family company, Lexcorp, invites kids from all over the country to attend an honors ceremony, Clark Kent is happy to participate. That is, until his awardtrophy creates a portal to another dimension and sucks him in! Lucky for Clark, his old friends Bruce and Diana along with newer friends Barry and Ollie are on the case! They'll have to travel to an alternate dimension to free their friend from Lex Luthor's grasp (and the worst detention ever)."--Provided by publisher.